Novel insights on remnant stomach following Roux-en-Y gastric bypass surgery based on histological evaluation and quantitative proteomics analysis - Carl I. W. Larson; Lars Fändriks; Anna Casselbrant; Ville Wallenius (Scientific Reports)
Abstract Patients undergoing weight-reducing Roux-en-Y gastric bypass (RYGB) have immediate positive effects on metabolic health, including type 2 diabetes (T2D). Refeeding via the secluded stomach, either by a gastrotube or after gastro-gastric fistulation result in T2D relapse and weight regain. The stomach therefore seems to play an active role in metabolism. To explore histological and protein expression changes in the gastric mucosa before compared to after RYGB. Perioperatively, biopsies were taken in a non-paired manner from the stomach (fundus, corpus, antrum) in patients undergoing Sleeve Gastrectomy (SG) and patients > 8 months postoperatively after RYGB by balloon-enteroscopy. The included SG and RYGB patients did not display any obvious mucosal or luminal pathology during surgery or the balloon-enteroscopies. The gastric biopsies both at perioperatively and postoperatively were prepared för histological evaluation and for quantitative (comparative) non-targeted proteomics. The results were compared by Volcano plots, Principal Component Analysis and STRING functional protein association networks. Histologically the gastric mucosa looked normal in biopsies from all the different parts of the postoperative bypassed stomach with no clear differences compared to the perioperative samples. The perioperative biopsies generally contained significantly higher amounts of proteins involved in fatty acid metabolism, oxidative phosphorylation and ATP metabolic processes, citric acid cycle and the respiratory chain. Postoperative biopsies instead showed overall increased quantities of proteins associated with ribosomes, RNA-metabolic processes, the mitotic cycle and pancreatic secretion. The results provide novel insights into the mucosal proteome-changes in the secluded stomach following RYGB.